Preparation method and application of fluorine-doped carbon material

By optimizing the preparation process of fluorine-doped carbon materials, a dense and uniform protective layer is constructed, which solves the problems of zinc dendrites and hydrogen evolution corrosion reactions of zinc negative electrodes, and significantly improves the corrosion resistance and cycle stability of zinc negative electrodes.

CN119822357AActive Publication Date: 2025-04-15HARBIN INST OF TECH +1

Patent Information

Application Number
CN202510034958.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

In practical applications, zinc negative electrodes have problems with zinc dendrites and hydrogen evolution corrosion reactions, resulting in reduced battery coulomb efficiency and shortened cycle life.

Method used

By optimizing the preparation process of fluorine-doped carbon materials, a dense and uniform protective layer is built to block the direct contact between the electrolyte and the zinc negative electrode, inhibit the hydrogen evolution corrosion reaction, and regulate the uniform deposition of zinc ions.

Benefits of technology

It significantly improves the corrosion resistance and cycle stability of zinc negative electrodes, extends the cycle life of zinc ion batteries, and has a simple process and industrial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822357A_ABST
    Figure CN119822357A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a fluorine-doped carbon material, and relates to a preparation method and application of a carbon material. The method comprises the following steps: 1, preparing a sodium fluoride solution; 2, dropwise adding perchloric acid into the sodium fluoride solution to obtain a mixed solution; 3, adding a carbon material into the mixed solution; and 4, carrying out hydrothermal reaction to obtain the fluorine-doped carbon material. By optimizing the preparation process of the fluorine-doped carbon material, the compactness and uniformity of the protective layer are realized, the corrosion resistance and cycling stability of the zinc negative electrode are remarkably improved, and an important technical support is provided for large-scale application of the water-based zinc ion battery. The prepared zinc negative electrode with the fluorine-doped carbon coating on the surface is used as a negative electrode of an aqueous zinc ion battery. The fluorine-doped carbon material prepared by the invention can effectively improve the corrosion resistance and cycling stability of the zinc negative electrode, and provides technical support for large-scale application of the water-based zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a carbon material and application thereof. Background Art

[0002] With the continuous growth of energy demand and the advancement of sustainable development goals, the development and utilization of clean energy has become particularly important. Zinc-ion batteries, as a new type of aqueous energy storage device, have attracted widespread attention due to their low material cost, strong environmental friendliness and excellent safety performance. However, there are significant technical bottlenecks in the practical application of zinc anodes, which seriously limits their widespread application.

[0003] The main problems of zinc anode include the growth of zinc dendrites and hydrogen evolution corrosion reaction. The formation of dendrites is caused by the uneven deposition of zinc ions on the surface of the anode. These dendrites not only pierce the battery separator and cause short circuits, but also cause loss of active materials, thereby reducing the coulombic efficiency of the battery. In addition, the hydrogen evolution corrosion reaction of the zinc anode in the aqueous electrolyte consumes a large amount of electrolyte, and the generated gas causes battery expansion, thereby shortening the cycle life of the battery.

[0004] In response to the above problems, current research mainly focuses on electrolyte modification, diaphragm design and the construction of negative electrode protective layers. Among them, constructing a protective layer on the surface of the zinc negative electrode is considered to be the most direct and efficient solution. The material of this type of protective layer needs to have high mechanical strength, chemical stability and good zinc ion transmission ability. Existing research on protective layers is mostly focused on inorganic materials and polymer materials, but the performance of a single material often cannot fully meet actual needs. For example, although inorganic materials have excellent mechanical strength, they have poor ductility and are prone to cracking during long-term cycles; while polymer materials have good toughness, but their performance in inhibiting dendrites and corrosion resistance is relatively limited. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a preparation method of a fluorine-doped carbon material and application thereof.

[0006] The present invention optimizes the preparation process of fluorine-doped carbon materials, realizes the compactness and uniformity of the protective layer, significantly improves the corrosion resistance and cycle stability of the zinc negative electrode, and provides important technical support for the large-scale application of aqueous zinc-ion batteries. The fluorine-doped carbon material prepared by the present invention can effectively improve the corrosion resistance and cycle stability of the zinc negative electrode, and provides technical support for the large-scale application of aqueous zinc-ion batteries.

[0007] A method for preparing a fluorine-doped carbon material is specifically completed by the following steps:

[0008] 1. Add sodium fluoride into deionized water and stir magnetically to obtain a sodium fluoride solution;

[0009] 2. Under magnetic stirring conditions, adding perchloric acid dropwise into the sodium fluoride solution to obtain a mixed solution;

[0010] 3. Under magnetic stirring conditions, adding the carbon material to the mixed solution, followed by magnetic stirring, and then ultrasonic dispersion to obtain a dispersion;

[0011] 4. The dispersion is transferred to a reactor and subjected to hydrothermal reaction for a period of time. After the reaction is completed, a reaction product is obtained; the reaction product is washed and dried to obtain a fluorine-doped carbon material.

[0012] Beneficial effects of the present invention:

[0013] 1. The present invention optimizes the preparation process of fluorine-doped carbon materials, making them more efficient and suitable for large-scale applications; it provides more reliable and low-cost technical support for aqueous zinc-ion batteries; the zinc negative electrode with a fluorine-doped carbon coating on the surface prepared by the present invention has the advantages of long cycle life and good stability, and the coating preparation process is simple, and has industrial prospects;

[0014] Second, the present invention constructs a fluorine-doped carbon protective layer on the surface of the zinc negative electrode, which effectively blocks the direct contact between the electrolyte and the zinc negative electrode, inhibits the hydrogen evolution corrosion reaction, and at the same time regulates the uniform deposition of zinc ions, significantly reduces the growth risk of zinc dendrites, and improves the cycle stability of the battery;

[0015] 3. The Zn / / Zn symmetric battery assembled with the modified zinc anode (zinc anode with fluorine-doped carbon coating on the surface) can be used at 5 mA / cm 2 It can stably cycle for more than 4500 h at a current density of , which far exceeds the life of the symmetrical battery assembled with unmodified zinc anode (original zinc anode).

[0016] The invention can obtain a fluorine-doped carbon material and a zinc negative electrode with a fluorine-doped carbon coating on the surface. The zinc negative electrode with a fluorine-doped carbon coating on the surface is used as a negative electrode of an aqueous zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a scanning electron microscope image of the polypyrrole-derived carbon tube prepared in Example 1;

[0018] Figure 2 The transmission electron microscope image of the fluorine-doped carbon material prepared in Example 1 and the corresponding EDS energy spectrum distribution diagram of the fluorine element;

[0019] Figure 3 The F1s high-resolution X-ray photoelectron spectrum of the fluorine-doped carbon material prepared in Example 1;

[0020] Figure 4The F1s high-resolution X-ray photoelectron spectrum of the fluorine-doped carbon material prepared in Example 2;

[0021] Figure 5 The F1s high-resolution X-ray photoelectron spectrum of the fluorine-doped carbon material prepared in Example 3;

[0022] Figure 6 The symmetrical battery assembled using the zinc negative electrode with fluorine-doped carbon coating on the surface prepared in Example 1 was 2 、1mAh / cm 2 Time voltage graph under test conditions;

[0023] Figure 7 The symmetric cell assembled with the zinc anode modified by the commercial carbon nanotube prepared in Application Example 2 was 2 、1mAh / cm 2 Time-voltage graph under test conditions. DETAILED DESCRIPTION

[0024] Specific implementation method 1: This implementation method is a method for preparing a fluorine-doped carbon material, which is specifically completed by the following steps:

[0025] 1. Add sodium fluoride into deionized water and stir magnetically to obtain a sodium fluoride solution;

[0026] 2. Under magnetic stirring conditions, adding perchloric acid dropwise into the sodium fluoride solution to obtain a mixed solution;

[0027] 3. Under magnetic stirring conditions, adding the carbon material to the mixed solution, followed by magnetic stirring, and then ultrasonic dispersion to obtain a dispersion;

[0028] 4. The dispersion is transferred to a reactor and subjected to hydrothermal reaction for a period of time. After the reaction is completed, a reaction product is obtained; the reaction product is washed and dried to obtain a fluorine-doped carbon material.

[0029] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the concentration of the sodium fluoride solution in step 1 is 100 mmol / L to 500 mmol / L; the speed of the magnetic stirring in step 1 is 800 r / min to 1000 r / min, and the magnetic stirring time is 30 min to 60 min. The other steps are the same as those in specific embodiment 1.

[0030] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the concentration of perchloric acid in step 2 is 0.01mol / L to 0.47mmol / L, and perchloric acid is added dropwise to the sodium fluoride solution until the pH value of the mixed solution is 2 to 4, and the addition of perchloric acid is stopped; the speed of magnetic stirring in step 2 is 800r / min to 1000r / min. The other steps are the same as those in specific implementation method 1 or 2.

[0031] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the speed of the magnetic stirring in step 3 is 800 r / min to 1000 r / min, and the time of the magnetic stirring is 60 min to 90 min; the mass ratio of the carbon material in step 3 to the volume ratio of the mixed solution is (40 mg to 60 mg): (80 mL to 120 mL); the time of the ultrasonic dispersion in step 3 is 60 min to 90 min, and the power of the ultrasonic dispersion is 160 W to 180 W. The other steps are the same as those in specific embodiments 1 to 3.

[0032] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the carbon material described in step 3 is one or more of polypyrrole-derived carbon tubes, carbon nanotubes, porous carbon, graphene, graphite, activated carbon, carbon black, carbon fiber, carbon quantum dots or carbon-based composite materials. The other steps are the same as specific embodiments 1 to 4.

[0033] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the preparation method of the polypyrrole-derived carbon tube is completed in the following steps:

[0034] ①, add methyl orange to deionized water, and then stir in a water bath until the methyl orange is completely dissolved to obtain a methyl orange solution;

[0035] The concentration of the methyl orange solution in step ① is 15 mmol / L to 30 mmol / L; the temperature of the water bath heating in step 1 is 60° C. to 80° C.

[0036] ②, adding pyrrole monomer and p-toluenesulfonic acid to the methyl orange solution, stirring with magnetic force to obtain a mixed solution;

[0037] The volume ratio of the pyrrole monomer to the methyl orange solution in step ② is (300 μL to 400 μL): (80 mL to 120 mL);

[0038] The volume ratio of the mass of p-toluenesulfonic acid described in step ② to the methyl orange solution is (120mg~150mg):(80mL~120mL);

[0039] The speed of the magnetic stirring in step ② is 800 r / min to 1000 r / min, and the time of the magnetic stirring is 60 min to 90 min;

[0040] ③. Add ferric chloride to deionized water and stir magnetically to obtain a ferric chloride solution; stir the ferric chloride solution magnetically in an ice bath for a period of time, then dropwise add the solution to the mixed solution, and continue stirring in an ice water bath for a period of time to obtain a solid reactant I; wash and dry the solid reactant I to obtain a solid reactant II;

[0041] The concentration of the ferric chloride solution described in step ③ is 40mmol / L to 60mmol / L;

[0042] The speed of the magnetic stirring in step ③ is 500r / min to 1000r / min, and the time of the magnetic stirring is 10min to 30min;

[0043] In step ③, the ferric chloride solution is magnetically stirred in an ice bath for 1 h to 2 h;

[0044] The volume ratio of the ferric chloride solution described in step ③ to the methyl orange solution in the mixed solution is (15mL-25mL):(80mL-120mL);

[0045] In step ③, the stirring speed is 700 r / min to 900 r / min under ice water bath conditions, and the stirring time is 24 h to 36 h;

[0046] In step ③, the solid reactant I is washed with deionized water until the washing solution is colorless; in step ③

[0047] The drying temperature is 70°C to 90°C, and the drying time is 8h to 10h;

[0048] ④, transferring the solid reactant II to a tube furnace, raising the temperature to a calcination temperature under an inert gas atmosphere, calcining at the calcination temperature for a period of time, and grinding into particles after calcination to obtain polypyrrole-derived carbon tubes;

[0049] The inert gas in step ④ is nitrogen, argon, helium or a mixture of the above;

[0050] The heating rate in step ④ is 2°C / min to 10°C / min;

[0051] The calcination temperature in step ④ is 700° C. to 900° C., and the calcination time is 60 min to 100 min. The other steps are the same as those in specific embodiments 1 to 5.

[0052] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the temperature of the hydrothermal reaction in step 4 is 150°C to 180°C, and the time of the hydrothermal reaction is 15h to 24h; in step 4, the reaction product is washed with deionized water until the reaction product is neutral; the drying temperature in step 4 is 60°C to 80°C, and the drying time is 10h to 16h. The other steps are the same as those in specific embodiments 1 to 6.

[0053] Specific implementation method eight: This implementation method is a fluorine-doped carbon material used to modify the zinc negative electrode.

[0054] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: a fluorine-doped carbon material is used to modify the zinc negative electrode, which is specifically completed by the following steps:

[0055] 1. dispersing the fluorine-doped carbon material and the adhesive in a solvent to obtain a dispersion;

[0056] The solvent in step 1 is one or a mixture of several of N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, dichloromethane and ethanol;

[0057] The binder described in step 1 is one or a mixture of polyvinylidene fluoride, polyacrylic acid, sodium carboxymethyl cellulose, styrene-butadiene rubber, chitosan and polyurethane;

[0058] The mass ratio of the fluorine-doped carbon material to the adhesive in step 1 is (8-9):(1-2);

[0059] Step 1: The mass fraction of the fluorine-doped carbon material in the dispersion is 20% to 60%;

[0060] 2. coating the dispersion onto the surface of the zinc negative electrode and drying the dispersion to obtain a zinc negative electrode having a fluorine-doped carbon coating on the surface;

[0061] The drying temperature in step 2 is 60°C to 80°C;

[0062] In step 2, the thickness of the fluorine-doped carbon coating on the surface of the zinc negative electrode is 5 μm to 30 μm. The other steps are the same as those in specific embodiments 1 to 8.

[0063] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the zinc negative electrode with a fluorine-doped carbon coating on the surface described in step 2 is used as the negative electrode of the aqueous zinc ion battery. The other steps are the same as those of specific embodiments 1 to 9.

[0064] The following examples are used to verify the beneficial effects of the present invention:

[0065] Example 1: A method for preparing a polypyrrole-derived carbon tube-modified zinc negative electrode is specifically completed by the following steps:

[0066] 1. Preparation of carbon materials;

[0067] ①, add methyl orange to deionized water, and then stir in a water bath at 80°C until the methyl orange is completely dissolved to obtain a methyl orange solution;

[0068] The concentration of the methyl orange solution described in step ① is 15 mmol / L;

[0069] ②, add 350 μL of pyrrole monomer and 140 mg of p-toluenesulfonic acid into 100 mL of methyl orange solution, and stir magnetically for 60 min at a speed of 800 r / min to obtain a mixed solution;

[0070] ③. Add ferric chloride to deionized water, and then stir the mixture for 30 minutes at a magnetic stirring speed of 1000 r / min to obtain a ferric chloride solution; stir the ferric chloride solution for 1 hour at an ice bath temperature of 0°C and a magnetic stirring speed of 800 r / min, then drop 20 mL of the ferric chloride solution into the mixed solution obtained in step 2, and continue stirring the mixture for 24 hours at a magnetic stirring speed of 800 r / min and an ice bath temperature to obtain a solid reactant I; wash the solid reactant I three times with deionized water, and then dry it at 70°C for 10 hours to obtain a solid reactant II;

[0071] The concentration of the ferric chloride solution described in step ③ is 50mmol / L;

[0072] ④, transferring the solid reactant II to a tube furnace, heating it to 800°C in a nitrogen atmosphere, calcining it at 800°C for 80 minutes, and grinding it into particles after calcination to obtain polypyrrole-derived carbon tubes, i.e., carbon materials;

[0073] The heating rate in step ④ is 5°C / min;

[0074] 2. Add sodium fluoride to 100 mL of deionized water, and then stir the mixture under magnetic stirring at a speed of 1000 r / min for 30 min to obtain a sodium fluoride solution;

[0075] The concentration of the sodium fluoride solution described in step 2 is 100mmol / L;

[0076] 3. Under the condition of stirring at a speed of 1000 r / min, adding perchloric acid dropwise into the sodium fluoride solution until the pH value of the mixed solution reaches 3, thereby obtaining a mixed solution;

[0077] The concentration of perchloric acid described in step 3 is 0.06mmol / L;

[0078] 4. Under magnetic stirring conditions, 50 mg of the carbon material prepared in step 1④ was added to the mixed solution, followed by magnetic stirring for 60 min, and then ultrasonic dispersion for 60 min to obtain a dispersion;

[0079] 5. Transfer the dispersion to a reactor and perform a hydrothermal reaction at 160°C for 16 hours. After the reaction is completed, a reaction product is obtained. The reaction product is washed with deionized water until it is neutral, and then dried at 60°C for 12 hours to obtain a fluorine-doped carbon material.

[0080] Figure 1 is a scanning electron microscope image of the polypyrrole-derived carbon tube prepared in Example 1;

[0081] Figure 2 The transmission electron microscope image of the fluorine-doped carbon material prepared in Example 1 and the corresponding EDS energy spectrum distribution diagram of the fluorine element;

[0082] from Figure 2 It can be seen that the morphology and structure of the fluorine-doped carbon material prepared in Example 1 are not destroyed compared with that before doping (polypyrrole-derived carbon tubes), and obvious uniform distribution of fluorine elements can be observed.

[0083] Figure 3 The F1s high-resolution X-ray photoelectron spectrum of the fluorine-doped carbon material prepared in Example 1;

[0084] from Figure 3 It can be seen that the fluorine-doped carbon material prepared in Example 1 can detect obvious fluorine element signals, which once again confirms the successful doping of fluorine element.

[0085] Example 2: The difference between this example and Example 1 is that the sodium fluoride solution in step 2 is 10 mmol / L. The other steps and parameters are the same as those in Example 1.

[0086] Figure 4 The F1s high-resolution X-ray photoelectron spectrum of the fluorine-doped carbon material prepared in Example 2;

[0087] from Figure 4 It can be seen that no obvious fluorine element signal can be detected in the fluorine-doped carbon material prepared in Example 2, proving that effective fluorine doping cannot be performed when the concentration of the sodium fluoride solution is too low.

[0088] Example 3: The difference between this example and Example 1 is that the sodium fluoride solution in step 2 is 1000 mmol / L. The other steps and parameters are the same as those in Example 1.

[0089] Figure 5 The F1s high-resolution X-ray photoelectron spectrum of the fluorine-doped carbon material prepared in Example 3;

[0090] from Figure 5 It can be seen that the morphology and structure of the fluorine-doped carbon material prepared in Example 3 is destroyed, which proves that too high a concentration of the sodium fluoride solution will increase the destructive effect on the morphology and structure of the carbon material.

[0091] Application Example 1: The zinc negative electrode is modified using the fluorine-doped carbon material prepared in Example 1, specifically by the following steps:

[0092] 1. Dispersing 20 mg of the fluorine-doped carbon material prepared in Example 1 and polyvinylidene fluoride in 100 μL of N-methylpyrrolidone to obtain a dispersion;

[0093] The mass ratio of the fluorine-doped carbon material to polyvinylidene fluoride described in step 1 is 9:1;

[0094] 2. Use sandpaper to polish the zinc negative electrode with a thickness of 100 μm to make it bright, remove the oxide layer, adjust the coating thickness of the coater to 150 μm, and then apply the dispersion to the surface of the polished zinc negative electrode, and dry it at 80°C for 12 hours to obtain a zinc negative electrode with a fluorine-doped carbon coating on the surface.

[0095] Figure 6 The symmetrical battery assembled using the zinc negative electrode with fluorine-doped carbon coating on the surface prepared in Example 1 was 2 、1mAh / cm 2 Time voltage graph under test conditions;

[0096] from Figure 6 It can be seen that compared with the symmetrical battery composed of untreated pure zinc sheets, the cycle life of the symmetrical battery composed of fluorine-doped carbon material modified zinc negative electrode is significantly improved, with a stable cycle of more than 4500h. During the entire cycle, there is no obvious fluctuation in the polarization voltage, showing extremely excellent cycle stability, which strongly proves the advantages of fluorine-doped carbon material modified zinc negative electrode.

[0097] Application Example 2: Modification of zinc negative electrode using commercial carbon nanotubes is carried out in the following steps:

[0098] 1. Dispersing 20 mg of commercial carbon nanotubes (prepared by chemical vapor deposition) and polyvinylidene fluoride sold by McLean in 100 μL of N-methylpyrrolidone to obtain a dispersion;

[0099] The mass ratio of the commercial carbon nanotubes to polyvinylidene fluoride described in step 1 is 9:1;

[0100] 2. Use sandpaper to polish the zinc negative electrode with a thickness of 100 μm to make it bright and remove the oxide layer. Adjust the coating thickness of the coater to 150 μm, and then apply the dispersion to the surface of the polished zinc negative electrode. Dry it at 80 °C for 12 hours to obtain a commercial carbon nanotube-modified zinc negative electrode.

[0101] Figure 7 The symmetric cell assembled with the zinc anode modified by the commercial carbon nanotube prepared in Application Example 2 was 2 、1mAh / cm 2 Time voltage graph under test conditions;

[0102] from Figure 7 It can be seen that the symmetrical battery assembled with the zinc negative electrode modified by carbon nanotubes short-circuited after only about 200 hours of cycling, proving that it cannot effectively improve the cycle life of the zinc negative electrode.

Claims

1. A method for preparing a fluorine-doped carbon material, characterized in that The preparation method is specifically completed according to the following steps:

1. Add sodium fluoride into deionized water and stir magnetically to obtain a sodium fluoride solution; 2. Under magnetic stirring conditions, adding perchloric acid dropwise into the sodium fluoride solution to obtain a mixed solution; 3. Under magnetic stirring conditions, adding the carbon material to the mixed solution, followed by magnetic stirring, and then ultrasonic dispersion to obtain a dispersion; 4. The dispersion is transferred to a reactor and subjected to hydrothermal reaction for a period of time. After the reaction is completed, a reaction product is obtained; the reaction product is washed and dried to obtain a fluorine-doped carbon material.

2. The method for preparing a fluorine-doped carbon material according to claim 1, characterized in that The concentration of the sodium fluoride solution described in step 1 is 100 mmol / L to 500 mmol / L; the speed of the magnetic stirring described in step 1 is 800 r / min to 1000 r / min, and the time of the magnetic stirring is 30 min to 60 min.

3. The method for preparing a fluorine-doped carbon material according to claim 1, characterized in that The concentration of the perchloric acid in step 2 is 0.01 mol / L to 0.47 mmol / L. In step 2, the perchloric acid is added dropwise to the sodium fluoride solution until the pH value of the mixed solution is 2 to 4, and the addition of the perchloric acid is stopped. The speed of the magnetic stirring in step 2 is 800 r / min to 1000 r / min.

4. The method for preparing a fluorine-doped carbon material according to claim 1, characterized in that The speed of the magnetic stirring described in step three is 800r / min~1000r / min, and the time of the magnetic stirring is 60min~90min; the volume ratio of the mass of the carbon material described in step three to the mixed solution is (40mg~60mg):(80mL~120mL); the time of the ultrasonic dispersion described in step three is 60min~90min, and the power of the ultrasonic dispersion is 160W~180W.

5. The method for preparing a fluorine-doped carbon material according to claim 1, characterized in that The carbon material described in step three is one or more of polypyrrole-derived carbon tubes, carbon nanotubes, porous carbon, graphene, graphite, activated carbon, carbon black, carbon fiber, carbon quantum dots or carbon-based composite materials.

6. The method for preparing a fluorine-doped carbon material according to claim 5, characterized in that The method for preparing the polypyrrole-derived carbon tubes is specifically completed by the following steps: ①, add methyl orange to deionized water, and then stir in a water bath until the methyl orange is completely dissolved to obtain a methyl orange solution; The concentration of the methyl orange solution in step ① is 15 mmol / L to 30 mmol / L; the temperature of the water bath heating in step 1 is 60° C. to 80° C.; ②, adding pyrrole monomer and p-toluenesulfonic acid to the methyl orange solution, stirring with magnetic force to obtain a mixed solution; The volume ratio of the pyrrole monomer to the methyl orange solution in step ② is (300 μL to 400 μL): (80 mL to 120 mL); The volume ratio of the mass of p-toluenesulfonic acid described in step ② to the methyl orange solution is (120mg~150mg):(80mL~120mL); The speed of the magnetic stirring in step ② is 800 r / min to 1000 r / min, and the time of the magnetic stirring is 60 min to 90 min; ③. Add ferric chloride to deionized water and stir magnetically to obtain a ferric chloride solution; The ferric chloride solution is magnetically stirred for a period of time in an ice bath, and then added dropwise to the mixed solution, and stirred for a period of time in an ice water bath to obtain a solid reactant I; The solid reactant I is washed and dried to obtain a solid reactant II; The concentration of the ferric chloride solution described in step ③ is 40mmol / L to 60mmol / L; The speed of the magnetic stirring in step ③ is 500r / min to 1000r / min, and the time of the magnetic stirring is 10min to 30min; In step ③, the ferric chloride solution is magnetically stirred in an ice bath for 1 h to 2 h; The volume ratio of the ferric chloride solution described in step ③ to the methyl orange solution in the mixed solution is (15mL-25mL):(80mL-120mL); In step ③, the stirring speed is 700 r / min to 900 r / min under ice water bath conditions, and the stirring time is 24 h to 36 h; In step ③, the solid reactant I is washed with deionized water until the washing solution is colorless; the drying temperature in step ③ is 70° C. to 90° C., and the drying time is 8 h to 10 h; ④, transferring the solid reactant II to a tube furnace, raising the temperature to a calcination temperature under an inert gas atmosphere, calcining at the calcination temperature for a period of time, and grinding into particles after calcination to obtain polypyrrole-derived carbon tubes; The inert gas in step ④ is nitrogen, argon, helium or a mixture of the above; The heating rate in step ④ is 2°C / min to 10°C / min; The calcination temperature in step ④ is 700° C. to 900° C., and the calcination time is 60 min to 100 min.

7. The method for preparing a fluorine-doped carbon material according to claim 1, characterized in that The temperature of the hydrothermal reaction described in step 4 is 150°C to 180°C, and the time of the hydrothermal reaction is 15h to 24h; in step 4, the reaction product is washed with deionized water until the reaction product is neutral; the drying temperature described in step 4 is 60°C to 80°C, and the drying time is 10h to 16h.

8. A method for preparing a fluorine-doped carbon material prepared by the preparation method according to claim 1, characterized in that A fluorine-doped carbon material is used to modify the zinc negative electrode.

9. The use of a fluorine-doped carbon material according to claim 8, characterized in that A fluorine-doped carbon material is used to modify a zinc negative electrode, which is specifically completed in the following steps:

1. dispersing the fluorine-doped carbon material and the adhesive in a solvent to obtain a dispersion; The solvent in step 1 is one or a mixture of several of N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, dichloromethane and ethanol; The binder described in step 1 is one or a mixture of polyvinylidene fluoride, polyacrylic acid, sodium carboxymethyl cellulose, styrene-butadiene rubber, chitosan and polyurethane; The mass ratio of the fluorine-doped carbon material to the adhesive in step 1 is (8-9):(1-2); Step 1: The mass fraction of the fluorine-doped carbon material in the dispersion is 20% to 60%; 2. coating the dispersion onto the surface of the zinc negative electrode and drying the dispersion to obtain a zinc negative electrode having a fluorine-doped carbon coating on the surface; The drying temperature in step 2 is 60°C to 80°C; In step 2, the thickness of the fluorine-doped carbon coating on the surface of the zinc negative electrode is 5 μm to 30 μm.

10. The use of a fluorine-doped carbon material according to claim 9, characterized in that The zinc negative electrode with a fluorine-doped carbon coating on the surface described in step 2 is used as the negative electrode of an aqueous zinc ion battery.

Citation Information

Patent Citations

  • Carbon fluoride and application thereof

    CN102723490A

  • Three-dimensional array carbon nanotube and preparation method thereof

    CN115367737A

  • Preparation method and use method of phenanthrenequinone modified porous carbon nanotube supercapacitor material

    CN115642041A

  • Preparation method of fluorinated soft carbon with ultra-high specific energy, and use of primary lithium battery

    GB202217502D0

  • Solid electrochemical supercapacitor

    US20150009605A1

Cited By

  • Modified conductive carbon, slurry, positive electrode, battery and preparation method of modified conductive carbon

    CN121885633A